The Break between Old and New Orders in Laclau’s Theory of Hegemony - Kim, Min Seong (Problemos, 2023)
Drawing inspiration from Alain Badiou’s philosophical project of thinking radical change and novelty, this paper raises the question of whether Ernesto Laclau’s theory of hegemony provides an adequate conceptualization of social change. Laclau claims that the transition between old and new hegemonic formations constitutes a “radical break.” However, it shall be shown that Laclau’s claim apropos radical break is in tension with his elaboration of the conditions under which a particularity – including particular political projects or social orders – may become hegemonic. As a result, how a process of transformation is to be conceptually distinguished from a process of reproduction is left unclear within the hegemony theory.